Sosialisasi Potensi Beberapa Varietas Sorgum sebagai Bahan Baku Makanan Olahan - Eka Candra Lina; Wenny Surya Murtius (Warta Pengabdian Andalas, 2020)
Sorghum farmers in West Sumatra, especially Padang Pariaman, have low knowledge of sorghum varieties in plants. This is because sorghum relatively new food commodity cultivated in this area. The three varieties of sorghum that are often grown by farmers are numbu, Super 1, and red varieties, which differ in morphology, texture, and taste. The general procedure for harvesting sorghum begins with cutting panicles, drying them in the sun, threshing them, and drying them again until the moisture content reaches 12%. Then the sorghum seeds are crushed using a sosoh machine so that the tannin in the outer skin layer is lost. After going through the filling process, sorghum rice is produced, can be consumed directly by cooking it into porridge, cooked like rice, or mixed with rice (rasgum). Sorghum rice can also be ground into flour and used as a base for making various types of food. The community service team has carried out a chemical analysis of sorghum flour. There are amylose and amylopectin analysis, starch content analysis, starch gelatinization profile, and reducing sugar. The objective of this activity is to transfer knowledge and technology related to sorghum rice and sorghum flour as raw materials for food processing. From the data obtained, known that red sorghum has the best performance as raw material for wet-processed food, while Numbu and Super 1 are suitable as raw materials for dry processed food.